The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1001/jamanetworkopen.2022.54669
|View full text |Cite
|
Sign up to set email alerts
|

Association of Anthracycline With Heart Failure in Patients Treated for Breast Cancer or Lymphoma, 1985-2010

Abstract: ImportanceAnthracyclines increase the risk for congestive heart failure (CHF); however, long-term cumulative incidence and risk factors for CHF after anthracycline therapy are not well defined in population-based studies.ObjectiveTo compare the long-term cumulative incidence of CHF in patients with breast cancer or lymphoma treated with anthracycline therapy compared with healthy controls from the same community.Design, Setting, and ParticipantsThis retrospective population-based case-control study included da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 41 publications
1
19
1
1
Order By: Relevance
“…Interestingly, there was also no significant difference in risk based on the cumulative dose of anthracycline. While several other studies evaluating the incidence of CHF in patients with cancer exposed to anthracyclines have published similar results, the study by Larsen et al is unique and distinctly adds to our understanding of the epidemiology of anthracycline-associated CHF, given the long-term follow-up and the inclusion of both patients with breast cancer and lymphoma. Moreover, Larsen et al define CHF using the modified Framingham criteria and performed manual record review to confirm the CHF diagnosis, which contributes to the reliability of the conclusions.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…Interestingly, there was also no significant difference in risk based on the cumulative dose of anthracycline. While several other studies evaluating the incidence of CHF in patients with cancer exposed to anthracyclines have published similar results, the study by Larsen et al is unique and distinctly adds to our understanding of the epidemiology of anthracycline-associated CHF, given the long-term follow-up and the inclusion of both patients with breast cancer and lymphoma. Moreover, Larsen et al define CHF using the modified Framingham criteria and performed manual record review to confirm the CHF diagnosis, which contributes to the reliability of the conclusions.…”
supporting
confidence: 88%
“…Larsen et al 1 found no association between anthracycline dose and CHF diagnosis, although previous studies have suggested left ventricular (LV) dysfunction is associated with higher cumulative anthracycline exposure. 5 It is important to note that there was no imaging assessment of LV function in the study by Larsen et al 1 Moreover, the use of traditional cardioprotective medications, including β-blockers, statins, and angiotensin converting enzyme inhibitors or angiotensin receptor blockers, was not associated with a reduction in CHF. CHF symptoms can occur in the setting of both a normal and reduced LV ejection fraction, and the Rochester Epidemiology Project population represents a combination of both disease phenotypes.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…In the Original Investigation titled “Association of Anthracycline With Heart Failure in Patients Treated for Breast Cancer or Lymphoma, 1985-2010,” 1 published February 3, 2023, there was an error in Dr Goetz’s affiliation, which should have been Division of Medical Oncology, Mayo Clinic, Rochester, Minnesota. This article has been corrected.…”
mentioning
confidence: 99%